Spectrum of HBB gene variants and major endocrine complications in thalassemia patients of Pakistan - Muhammad Bilal Ghafoor; Ikram Din Ujjan; Ali Muhammad Waryah; Faheem Ahmed Memon (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine the molecular characterisation of beta-thalassemia major patients, pattern of major endocrine complications and its association with haemoglobin subunit beta gene variants. Method: The cross-sectional study was conducted from November 2021 to November 2022 after approval from the ethics review committee of Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan, and comprised of 88 patients with beta thalassemia major aged >8 years and having serum ferritin level >1000µg/L. The subjects were analysed for haemoglobin subunit beta gene variants and major endocrine complications, like growth retardation, hypogonadism, hypothyroidism, hypoparathyroidism and diabetic abnormalities using an automatic chemistry analyser, fully automatic chemiluminescence immunoassay analyser, enzyme-linked immunosorbent assay and real-time polymerase chain reaction. Data was analysed using SPSS 25. Results: Of the 88 subjects, 40(45.4%) were girls and 48(54.5%) were boys. The overall mean age was 12±2.81 years. Of the total, 55(62.5%) had growth retardation, 41(46.6%) were cases of hypogonadism, 16(18.1%) hypothyroidism, 5(5.7%) hypoparathyroidism, 3(3.4%) diabetes mellitus and 8 (9.1%) had impaired glucose tolerance. Also, 65(73.9%) patients confronted at least one endocrine complication. Endocrine complications were strongly associated with serum ferritin levels (p=0.000). The most common haemoglobin subunit beta gene variant identified was IVSI-5 (G>C) in 36(40.9%), and the least identified variant was cluster of differenctiation-26 (G>A) 1(1.1%). The association between haemoglobin subunit beta gene variants with endocrine complications was statistically non-significant (p>0.05). Conclusion: IVSI-5 (G>C) was found to be the most frequent haemoglobin subunit beta gene variant among beta-thalassemia major patients. Key Words: Beta-thalassemia major, Endocrine complications, Growth retardation, Hypothyroidism, Parathyroidism, Diabetes mellitus.